2003
DOI: 10.1161/01.cir.0000104569.96907.7f
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Stenosis After Radiofrequency Ablation of Atrial Fibrillation

Abstract: Background-Pulmonary vein (PV) stenosis is a complication of ablation for atrial fibrillation. The impact of different ablation strategies on the incidence of PV stenosis and its functional characterization has not been described. Methods and Results-PV isolation was performed in 608 patients. An electroanatomic approach was used in 71 and circular mapping in 537 (distal isolation, 25; ostial isolation based on PV angiography, 102; guided by intracardiac echocardiography, 140; with energy delivery based on vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(54 citation statements)
references
References 29 publications
1
52
0
1
Order By: Relevance
“…In previous studies that were performed during the initial AF ablation era, the prevalence of PV stenosis was reported to be 3% to 42%. [4][5][6][7][8] Since then, the prevalence has decreased to 0.3% as the ablation site has shifted toward the left atrium (LA) 9 and with the optimization of radiofrequency energy and technical improvements that have been achieved by confirming the catheter position with a 3-dimensional electroanatomical mapping system. Although most cases of PV stenosis are asymptomatic, severe PV stenosis can progress to complete occlusion with potentially life-threatening symptoms of segmental pulmonary hypertension or venous infarction of the corresponding lobe.…”
mentioning
confidence: 99%
“…In previous studies that were performed during the initial AF ablation era, the prevalence of PV stenosis was reported to be 3% to 42%. [4][5][6][7][8] Since then, the prevalence has decreased to 0.3% as the ablation site has shifted toward the left atrium (LA) 9 and with the optimization of radiofrequency energy and technical improvements that have been achieved by confirming the catheter position with a 3-dimensional electroanatomical mapping system. Although most cases of PV stenosis are asymptomatic, severe PV stenosis can progress to complete occlusion with potentially life-threatening symptoms of segmental pulmonary hypertension or venous infarction of the corresponding lobe.…”
mentioning
confidence: 99%
“…Progression of stenosis was variable. Saad et al reported 8.8% progression mainly in first 3 months and regression in 10.4% [38].…”
Section: Atrial Fibrillation Ablationmentioning
confidence: 96%
“…In 2002, Arentz et al showed 28% incidence of PVS, which in later studies declined to 0.1–1.3% [22], [35], [36] and only 0.29% needed intervention [37]. This decreasing incidence was due to changing ablation site from pulmonary vein lumen to antrum, reducing power of ablation and adopting additional imaging modalities to better delineate the ostial anatomy [38], [39]. Dong et al showed that encircling individual veins carried more risk compared to encircling ipsilateral pairs [40].…”
Section: Atrial Fibrillation Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Delivery of energy within the PVs themselves led to unacceptable rates of PV stenosis. 23,24 As a result, various approaches have been used to, in effect, isolate the PVs. While other trigger areas exist, many are approaching focal ablations by targeting tissue around the orifices of the PVs.…”
Section: Catheter-based Approaches To Af Treatmentmentioning
confidence: 99%